Launching the Mission for 100 Climate Neutral Cities in Europe: Characteristics, Critiques, and Challenges - Shabb, Katherine; McCormick, Kes; Mujkic, Selma; Anderberg, Stefan; Palm, Jenny; Carlsson, Annica (Frontiers in Sustainable Cities, 2022)
The purpose of this perspective article is to critically explore the launch of the mission for 100 climate neutral cities in Europe. An overview of the mission approach in general is first presented, where key aspects and emerging critiques are identified. Second, key elements of the mission for 100 climate neutral cities in Europe are introduced along with some of its challenges and ambiguities. This perspective article ends with highlighting key emerging questions from the report “100 Climate Neutral Cities by 2030 – by and for the citizens” where research and practice need to engage to support municipalities and urban actors in efforts on climate neutrality and help to better navigate toward radical social and technical transformation. This perspective article also proposes two approaches for inclusive participation of citizens and stakeholders that can contribute to the local implementation of the mission for 100 climate neutral cities.